Bridging the Dialectical Histories in Organizational Change: Hysteresis in Scandinavian Telecommunications Privatization - Koll, Henrik (Nordic Journal of Working Life Studies, 2021)
Conventionally, organizational change research has viewed history as objective facts associated with path dependencies, making change difficult. However, started with the work of Suddaby et al. (2010), a different stance has emerged, viewing history as a subjective, narrative construction that can be utilized to facilitate change. This paper responds to calls for ways of bridging these two perceptions and increasing historical consciousness in organizational change studies. To these ends, the paper explores the capacity of Bourdieu’s construct of hysteresis as a bridging construct. Based on an ethnographic study, the paper operationalizes hysteresis to analyze the response strategies of technicians and shop stewards to organizational change following privatization in a Scandinavian telecommunications company. The paper argues that hysteresis constitutes a valuable alternative to bridging constructs available in extant literature and holds the potential to open new avenues for exploring the implications of history for organizational change.